Low-velocity impact on cylindrically curved bilayers. (December 2018) - Bidi, A; Liaghat, Gh; Rahimi, Gh
In this study, low-velocity impact response of cylindrically curved bilayer panels is studied. A large number of parameters affect the impact dynamics and many models have been used for solution previously. These models can be classified as energy balance model, spring–mass model, and complete models in which the dynamic behavior of the structure is exactly modeled. In this study, a two degrees of freedom spring–mass model is used to evaluate contact force between the composite panel and impactor. This work uses the modified Hertz contact model which is linearized form of general Hertz contact law. First-order shear deformation theory coupled with Fourier series expansion is used to derive the governing equations of the curved bilayer panel. The effects of panel curvature, impact velocity, and mass of impactor on the panel behavior under low-velocity impact are investigated. The results show that changing the panel radius of curvature will change the impact force, impact duration, and local panel deformation. Finally, analytical solutions have been compared with numerical results.